Rancang Bangun Aplikasi Pengajuan Cuti Karyawan Berbasis Web Dengan Metode Extreme Programming Pada PT. Continental Panjipratama - Muchamad Muchrodi; Perani Rosyani (CV. Shofanah Media Berkah, 2023)
PT. Continental Panjipratama is one of the companies engaged in manufacturing that produces various types of shoe products. One way the company can fulfill the rights of employees is to provide annual leave rights to employees in accordance with the provisions of Law No. 13 of 2003 concerning employment, Article 79 paragraph 2c. Until now PT. Continental Panjiprtama in handling its leave application is still done conventionally where in the process of submitting leave, employees fill out a form first to be approved by the head of department and company leadership. In addition, the storage of the leave submission report is still in the form of an archive, so that there is a buildup in the annual leave submission report. And there is no web-based employee leave application system yet. So that the process of applying for annual leave at PT. Continental Panjipratama is considered less effective and efficient. The purpose of this research is to produce a website-based employee leave application system that can be accessed at any time by employees of PT. Continental Panjipratama so that it can assist employees in the process of applying for leave. The development system method used in this research is the extreme programming method. This employee leave application system application is built using the PHP, HTML, MYSQL programming languages and the bootstrap framework. With the existence of a web- based employee leave application information system, it can assist employees in the leave application process which can be accessed anytime online.